Sistem Informasi Manajemen Aset (SIMASET) Perkebunan Kelapa Sawit pada PT. Treekreasi Margamulia Palembang - Eka Hartati Syamiri; Dedy Kurnianto; Selviani Maramis (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
PT. Treekreasi Margamulia is a company that eliminates oil palm plantations in the city of Palembang. In the processing of oil palm plantation Asset in PT. Treekeasi Margamulia conducted by the staff of finance. The data of the processed assets is data on fixed assets and asset data. The asset data does not yet have an integrated system. Data management related to procurement, use, maintenance, and depreciation of assets that have not been integrated lead to frequent loss and also the hassle of happiness and Company's need to upgrade the old system to switch to the system A new facility with the utilization of local server facilities in the company. To maximize the performance of financial staff in the company in the process of asset management, in order to present better report results and Efisen for the company leader. Research using the method of developing Rational Unified Process (RUP) system, with four phases namely, inception, elaboration, construction, and trantition, research results in the form of asset Management Information System (SIMASET) palm oil Plantation At PT. TreeKreasi Margamulia.